Current problems in cardio rheumatology and approach to treatment - Dilnura Tursunova Akram qizi; Zunira Eshonkulova Jamolidinovna; Fariza Sadikova Ashrafovna (Periodica Journal, 2025)
Cardiorheumatology is a branch of medicine that studies the interaction of cardiovascular and rheumatological diseases. This field, by analyzing the complex relationship between the cardiovascular system and rheumatic diseases, helps to develop new treatments aimed at improving the health of patients. This article provides information about the current problems of Cardiorheumatology and the approach to treatment.
Keywords: Cardiorheumatology; treatment; problem; patient